Novel Protein Domains and Repeats in Drosophila melanogaster: Insights into Structure, Function, and Evolution - Ponting, Chris P.; Mott, Richard; Bork, Peer; Copley, Richard R.

(untitled) (Genome Research, 2001)
Sequence database searching methods such asBLAST, are invaluable for predicting molecular function on the basis of sequence similarities among single regions of proteins. Searches of whole databases however, are not optimized to detect multiple homologous regions within a single polypeptide. Here we have used the prospero algorithm to perform self-comparisons of all predicted Drosophila melanogaster gene products. Predicted repeats, and their homologs from all species, were analyzed further to detect hitherto unappreciated evolutionary relationships. Results included the identification of novel tandem repeats in the human X-linked retinitis pigmentosa type-2 gene product, repeated segments in cystinosin, associated with a defect in cystine transport, and ‘nested’ homologous domains in dysferlin, whose gene is mutated in limb girdle muscular dystrophy. Novel signaling domain families were found that may regulate the microtubule-based cytoskeleton and ubiquitin-mediated proteolysis, respectively. Two families of glycosyl hydrolases were shown to contain internal repetitions that hint at their evolution via a piecemeal, modular approach. In addition, three examples of fruit fly genes were detected with tandem exons that appear to have arisen via internal duplication. These findings demonstrate how completely sequenced genomes can be exploited to further understand the relationships between molecular structure, function, and evolution.